Determinants of Stock Delisting (Analysis of Bankruptcy and Liquidity Ratios on Stock Delisting) - Syukra, Rahmiyatus; Riyanti, Agustina; Azizi, Ernes Septina (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This literature review analyzes bankruptcy and liquidity ratios on stock delisting. An update from previous research is that this study is expected to produce findings and innovations regarding the role of bankruptcy analysis and liquidity ratios on delisting of company shares. In the end, this research is expected to provide data and evidence of factors related to the determination of stock delisting. The bankruptcy analysis that the author discusses is bankruptcy analysis with the Altman Z-Score method, Springate method and Zmijewski Method. And the liquidity ratio that the author will discuss is the current ratio. Based on previous research, bankruptcy analysis using the Altman Z-Score, Springate and Zmijewski methods is said to be an indicator to assess the bankruptcy of a company and ultimately affect the delisting of the company's shares on the Indonesia Stock Exchange. And the most accurate method which has a percentage of 95% in predicting bankruptcy is the Altman Z-Score method. The Springate method has an accuracy rate of 92.5%. While the Zmijewski method is 94.9%. For the liquidity ratio, the authors try to conclude from previous research that the liquidity ratio measured using the current ratio has an influence on the company's financial distress, where financial distress is a condition where the company is said to be almost bankrupt.